Kaligrafi Asmaul Husna Dalam Karya Grafis - Dwika Prasetia; Irwan Irwan (Serupa The Journal of Art Education, 2020)
This final work visualizes Asmaul Husna's Calligraphy in Graphic Work, when forming the Names of Allah. It is hoped that Asmaul Husna's visualization will be able to have a positive influence, in the lives of oneself and society, through printed graphic arts (stencil print). The methods and processes of work used in the creation of the work include several stages: (1) al qudus; (2) elaboration; (3) synthesis; (4) concept realization; (5) finishing; discussion of graphic art works includes visualization of Asmaul Husna's. The titles of the works that were produced were: (1) Al-Qudus; (2) Al- Ali; (3) Al-Adl; (4) Al-Ghafar; (5) Al-Jami; (6) At-Tawwab; (7) Al-Hakim; (8) As-Salam; (9) Al-Kabir; (10) An-Nur ;.Kata Kunci :Asmaul Husna,seni grafis,